2015
DOI: 10.1007/s11010-015-2382-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-129-2 functions as a tumor suppressor in glioma cells by targeting HMGB1 and is down-regulated by DNA methylation

Abstract: MicroRNA (miRNA) dysregulation is causally related to cancer development and progression, and recent reports have revealed that DNA methylation constitutes an important mechanism for miRNA deregulation in cancer. MiR-129-2 has been reported to be down-regulated and functions as a tumor suppressor in a few human cancers. However, the involvement of miR-129-2 in the pathology of glioma and the mechanism underlying miR-129-2 regulation in glioma cells remain unclear. In this study, we performed quantitative PCR t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…In glioma cells, miR-129-2 could function as a tumor suppressor by targeting HMGB1. Reintroducing of miR-129-2 suppressed cell growth [46]. Consistently, restoration of miR-129-2 restrained glioma cell proliferation partially through repressing of some major oncogenic genes, such as PDGFRa and Foxp1 [47].…”
Section: Mir-129 and Cell Proliferationmentioning
confidence: 66%
See 3 more Smart Citations
“…In glioma cells, miR-129-2 could function as a tumor suppressor by targeting HMGB1. Reintroducing of miR-129-2 suppressed cell growth [46]. Consistently, restoration of miR-129-2 restrained glioma cell proliferation partially through repressing of some major oncogenic genes, such as PDGFRa and Foxp1 [47].…”
Section: Mir-129 and Cell Proliferationmentioning
confidence: 66%
“…In addition, the hypermethylation of the CpG island upstream of miR-129-2 in glioma patients led to the down-regulation of miR-129-2 by targeting HMGB1. Besides, demethylation of miR-129-2 by 5-Aza-dC treatment augmented miR-129-2 expression in glioma cells [46]. Several other studies also demonstrated that the downregulation of miR-129-2 was generally through chromatin remodeling and DNA methylation in glioma cells, and miR-129-2 expression could be restored upon treatment with trichostatin A (a histone deadetylase inhibitor) [47].…”
Section: Dna Methylation and Mir-129 Expressionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, their 3'-prime products are different, which are named miR-129-1-3p and miR-129-2-3p, respectively (6,7). Dysregulation of miR-129-2 is frequently detected in solid tumors (8)(9)(10)(11)(12)(13). However, the role of miR-129-2 in breast cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%